Crisis Response in Higher Education How the Pandemic Challenged University Operations and Organisation - Benner, Mats (Springer Nature, 2022)
This open access book explores the impact of Covid-19 on universities, and how students, staff, faculty and academic leaders have adapted to and dealt with the impact of the pandemic. Drawing on experiences from Britain, Australia and Sweden, it showcases how Covid has challenged routines and procedures in universities, and thrown them into a disarray of ever-changing events and short-term adaptations. The authors pay particular attention to how students, staff, faculty, and leaders have coped with Covid, through a series of autobiographical portraits of their strains but also heroic efforts in the harshest of circumstances. This important book explores the exceptional ramifications of the pandemic but also how universities may contribute to a fairer and more robust society and concludes with a set of prescriptions for universities that aim to be proactive and resilient forces in society. It will be of interest to scholars interested in higher education, governance and organizational studies. This is an open access book.